2007
DOI: 10.1038/sj.ijir.3901556
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and erectile dysfunction: meta-analysis of population-based studies

Abstract: Alcohol is long regarded as a risk factor for erectile dysfunction (ED), but epidemiological evidence has been equivocal. We aimed to investigate the ED risk associated with various levels of alcohol consumption by meta-analysis. We searched for population-based studies on ED through Medline, PubMed, PsychInfo, and scanned through reference lists. Eleven cross-sectional studies were included and analyzed with random effects model. We reviewed the results from one crosssectional study and two cohort studies. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 26 publications
4
54
0
4
Order By: Relevance
“…42,43 Excessive alcohol increases premature ejaculation, but studies clearly documenting increased ED are lacking. 41,44 Antioxidants Polyphenols are potent antioxidants found in high amounts in certain foods. Pomegranate has been shown to increase endothelial NO and prevent its breakdown.…”
Section: Excessive Alcoholmentioning
confidence: 99%
“…42,43 Excessive alcohol increases premature ejaculation, but studies clearly documenting increased ED are lacking. 41,44 Antioxidants Polyphenols are potent antioxidants found in high amounts in certain foods. Pomegranate has been shown to increase endothelial NO and prevent its breakdown.…”
Section: Excessive Alcoholmentioning
confidence: 99%
“…At low levels, alcohol can reduce inhibition and increase sexual desire (Cheng et al 2007); however, beyond the level of the guidelines, the depressive effects of alcohol are apparent (Bacon et al 2003;Arackal & Benegal 2007). In females who consume alcohol heavily, the likelihood of heavy or irregular menstrual periods, spontaneous abortion and infertility is greater when alcohol is consumed above the guideline levels (Bradley et al 1998).…”
Section: Sexual Dysfunction -mentioning
confidence: 99%
“…Traditionally, Mamajuana in Dominican Republic and Mead in Ireland have been used as aphrodisiacs. Although increased sexual arousal may be experienced by many who consume alcohol, studies have concluded negative effects of alcohol on sexual performance (Cheng, Ng, Chen, & Ko, 2007;Chew, 2009). Alcohol is a nervous system depressant, which can slow normal brain function, act as an anesthetic, and decrease blood circulation, thereby decreasing sensation and inhibiting normal erectile function and vaginal secretions (Peugh & Belenko, 2001).…”
Section: Alcoholmentioning
confidence: 99%